Slope Stability Analysis on Muaraenim Formation, South Sumatera, Indonesia - Ulhaque, Thaha Rizal; Khoirullah, Nur; Sophian, Raden Irvan; Zakaria, Zufialdi (Journal of Geological Sciences and Applied Geology, 2019)
Slope stability analysis is a necessary aspect in open mining operations. The research location is in the Muaraenim Formation, South Sumatra, Indonesia. In this study, the level of slope stability is determined by the value of the Safety Factor (FS). The method used is limit equilibrium, the Spencer method. The results of this study indicate that FS values are influenced by the angle of the slope, where with decreasing degree of slope, the FS value will increase. In addition, the FS value is also directly proportional to the cohesion value of the slope materials.